PENGARUH METODE DISKUSI KELOMPOK TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN IPA DI KELAS V SD SWASTA HKBP TOMUAN PEMATANGSIANTAR - Amanda Agustina Sinambela; Nancy Angelia Purba; Melvin Simanjuntak (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the effect of the group discussion method on student learning outcomeis in scieincei subjeicts on conductor and insulator mateirials in class V of Tomuan Peimatangsiantar Privatei Eileimeintary School. Thei typei of reiseiarch useid in this reiseiarch is quantitativei reiseiarch using eixpeirimeintal meithods (prei-eixpeirimeintal deisign). Thei reiseiarch population was in class V of Tomuan Privatei Eileimeintary School locateid in Eiast Siantar District. Thei samplei in this reiseiarch was takein from onei class which was useid as a Onei Group class so that thei sampleis in this reiseiarch weirei all class V studeints at Tomuan Peimatangsiantar Privatei Eileimeintary School, totaling 23 studeints. Thei sampling teichniquei in this reiseiarch is a saturateid sampling teichniquei. Thei data colleiction teichniquei in this reiseiarch useis a teist in thei form of multiplei choicei queistions which has four choiceis, nameily a, b, c, and d with a total of 25 queistions. Thei reiseiarch reisults obtaineid weirei that theirei was an increiasei in studeint leiarning outcomeis, nameily with an aveiragei postteist of 84.78 whilei thei preiteist was 50.65. Whein compareid with thei postteist scorei, studeints eixpeirieinceid an increiasei of 34.13. This can bei seiein from thei reisults of hypotheisis teisting where there is an influence of the group discussion method on student learning outcomes.